Benzimidazole analogs as WTA biosynthesis inhibitors targeting methicillin resistant Staphylococcus aureus. Issue 19 (1st October 2016) - Yang, Shu-Wei; Pan, Jianping; Yang, Christine; Labroli, Marc; Pan, Weidong; Caldwell, John; Ha, Sookhee; Koseoglu, Sandra; Xiao, Jing C.; Mayhood, Todd; Sheth, Payal R.; Garlisi, Charles G.; et al.
Graphical abstract: A series of benzimidazole analogs have been synthesized and displayed potent WTA inhibitory activity and antibacterial activity in combination with imipenem. Substitution on benzimidazole core has been explored to identify a potent WTA inhibitor21 . Abstract: A series of benzimidazole analogs have been synthesized to improve the profile of the previous lead compounds tarocin B and1 . The syntheses, structure–activity relationships, and selected biochemical data of these analogs are described. The optimization efforts allowed the identification of21, a fluoro-substituted benzimidazole, exhibiting potent TarO inhibitory activity and typical profile for a wall teichoic acid (WTA) biosynthesis inhibitor. Compound21 displayed a potent synergistic and bactericidal effect in combination with imipenem against diverse methicillin-resistant Staphylococci.